Development and Validation of a Survey to Measure Patients' Expectations of Wrist Arthritis Surgery - Wolff, Aviva L.; Mancuso, Carol A.; Lee, Steve K.; Wolfe, Scott W. (Journal of Wrist Surgery, 2022)
Background The purpose of this study was to develop and test a patient-derived expectations survey for wrist arthritis surgery. We hypothesized that preoperative patient expectations are higher in people with greater functional impairment and that postoperative fulfilment of patient expectations correlates with functional improvement.Methods The study was conducted in four phases.Development (n = 22) Preoperatively, patients were asked open-ended questions regarding expectations of surgery. A draft survey was then assembled.Reliability (n = 35) The survey was administered twice preoperatively. Concordance was measured with weighted kappa values and intraclass correlations (ICC).Validity (n = 58) Validity was assessed by comparing responses from the Expectations Survey to the patient-rated wrist evaluation (PRWE).Responsiveness (n = 18) Responsiveness was calculated by comparing the proportion of expectations fulfilled to PRWE scores 1-year postoperatively.Results Development Twenty-two distinct items representing the most frequent responses were utilized from the draft survey items of 1,244 expectations volunteered.Reliability Patients had high preoperative expectations of surgery (mean = 76.8); 30% had scores ≥90. Test–retest reliability was high (Cronbach α coefficients = 0.91, 0.93, ICC = 0.86). Endorsement of items = 66 to 100%; and weighted kappa values = 0.39 to 0.96.Validity Patients with greater preoperative expectations (≥63) had more pain, worse function, and worse PRWE scores than those with lower expectations.Responsiveness The proportion of fulfilled expectations was high (mean 0.80, median 0.79), and greater fulfillment (proportion > 0.80, n = 8) was associated with better postoperative PRWE scores.Conclusion The patient-derived expectations survey is reliable, valid, responsive, and addresses a spectrum of expectations for patients undergoing surgery for wrist arthritis.Clinical relevance Understanding patient expectations can contribute to customized care given the range of surgical choices for the arthritic wrist.
Keywords: expectations; wrist arthritis; patient-centered; outcomes